Entropia de Tsallis aplicada ao clima da terra. - Aviz, Sara Carolina Carrera de (2018)
Since the generalization of nonextensive statistical mechanics, it’s the concepts are being applied in several areas of science, such as the Earth’s climate. The weather of our planet is a very complex natural system with many variables that lead to properties that are not easy to compare with theorical models in the literature. Over a long period of time, it has been found that the earth has suffered changes due to climate transitions between glacial interglacials periods, which have often happened abruptly. In this job a study of the time series of deuterium corresponding to the time period which preceded the interglacial state in which we currently live. The work analyzes fluctuations in the concentration of deuterium to try to understand changes in the level of complexity of the earth’s climate over the period of time studied. Deuterium fluctuations are analyzed in light of the theory of non-extensive systems, in order to clarify the degree of extensiveness (or not) of the system. Time series of entropy for different parameters of non-extensivity are calculated. Finally, our data suggest that caculus of entropy can be an indicator of the emergence of critical transitions, at least in the studied system. The results are compared with others arising from the theory of critical slowing down, which represents an attempt to predict the approximation of the critical point. In summary, our study shows evidence that the earth’s climate can be considered a non-extensive system, and that in this system the entropy can be a interesting parameter for detecting critical climate changes.